The agrarian issue in the pedagogical practice of LEC/UFBA educational teachers: the challenge of implementing the working class schooling project - Janeide Bispo dos Santos (Universidade Federal do Norte do Tocantins, 2021)
This article presents the results of a research that analyzed the pedagogical work carried out by teachers graduated from the Course in Rural Education (LEC) at the Federal University of Bahia (UFBA). The contradictions of capitalist society are problematized to explain the repercussions on the working class in terms of exclusion and limitations in the access to material and cultural goods. The agrarian question is raised as a fundamental question of the capitalist society and its unfoldings on the working class. Rural Education is presented as a project of the working class whose aim is to face the structural order posed by bourgeois society. The pedagogical work of the research subjects is analyzed in the light of the four pillars that founded the Political Project of the Course (PPC), namely: consistent theoretical basis, political formation, class awareness, and revolutionary organization with insertion in class struggles with a look towards the pedagogical treatment given to the agrarian issue category, bearing in mind to confront the conception of the training and the teachers' practice in regards to the implementation of a revolutionary pedagogical practice. The research data reveals that not all teachers incorporated the conception of the content and method of the training to their respective practices.